Error recovery mechanism for grid-based workflow within SLA context. (15th November 2007) - Quan, Dang Minh
Service Level Agreements (SLAs) serve as a foundation for a reliable and predictable job execution at remote grid sites. In this paper, we describe an error recovery mechanism for workflow within the SLA context, coping with catastrophic failure when one or several High Performance Computing Centers (HPCCs) are detached from the grid system. We propose an algorithm to detect all affected sub-jobs when the error happens and an algorithm to remap those sub-jobs to the remaining healthy HPCCs with makespan optimise. The experiment result shows that our mechanism discovers a higher quality solution in a shorter time period than other existing methods.